2015
DOI: 10.4103/0974-2700.166663
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric open globe injury: A review of the literature

Abstract: Open globe injury (OGI) is a severe form of eye trauma estimated at 2-3.8/100,000 in the United States. Most pediatric cases occur at home and are the result of sharp object penetration. The aim of this article is to review the epidemiology, diagnosis, management, and prognosis of this condition by conducting a systematic literature search with inclusion of all case series on pediatric OGI published between 1996 and 2015. Diagnosis of OGI is based on patient history and clinical examination supplemented with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(23 citation statements)
references
References 92 publications
(140 reference statements)
5
16
1
Order By: Relevance
“… 18 Presentation to health care providers is thus often delayed, and affected children are placed at increased risk of developing post-traumatic endophthalmitis. 19 It is evident that further publicity is required to highlight this danger, and there is a strong argument to promote the use of protective eyewear for children playing with darts.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Presentation to health care providers is thus often delayed, and affected children are placed at increased risk of developing post-traumatic endophthalmitis. 19 It is evident that further publicity is required to highlight this danger, and there is a strong argument to promote the use of protective eyewear for children playing with darts.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies found that age has an important influence on visual acuity prognosis. 13 , 14 Additionally, a study by Agrawal et al 13 reported that the time lag between the injury onset and hospital admission was significantly associated with the final visual acuity of the patients. It appears that involvement of the posterior part of the globe is associated with poorer visual outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Penetrating eye trauma (open globe injury) occurs in 2 to 3.8/100,000 population in the United States. Posttraumatic endophthalmitis occurs in 0.9 to 18% of adults and 5 to 54% of children with such injuries (57,58). Risk factors include delay in treatment of the eye trauma, rural setting of the injury, presence of an intraocular foreign body, lens capsule disruption, and a lacerating injury rather than blunt trauma with globe rupture.…”
Section: Posttraumatic Endophthalmitismentioning
confidence: 99%